Personal exposures to fine particulate matter and carbon monoxide in relation to cooking activities in rural Malawi [version 2; peer review: 2 approved] - Martha Chinouya; Debora Makina; Kevin Mortimer; James Chirombo; Sean Semple; Henry Sambakunsi; Jamie Rylance; Sepeedeh Saleh; Moses Kumwenda (Wellcome Open Research, 2023)
Background: Air pollution is a major environmental risk factor for cardiorespiratory disease. Exposures to household air pollution from cooking and other activities, are particularly high in Southern Africa. Following an extended period of participant observation in a village in Malawi, we aimed to assess individuals’ exposures to fine particulate matter (PM2.5) and carbon monoxide (CO) and to investigate the different sources of exposure, including different cooking methods. Methods: Adult residents of a village in Malawi wore personal PM2.5 and CO monitors for 24-48 hours, sampling every 1 (CO) or 2 minutes (PM2.5). Subsequent in-person interviews recorded potential exposure details over the time periods. We present means and interquartile ranges for overall exposures and summaries stratified by time and activity (exposure). We employed multivariate regression to further explore these characteristics, and Spearman rank correlation to examine the relationship between paired PM2.5 and CO exposures. Results: Twenty participants (17 female; median age 40 years, IQR: 37–56) provided 831 hours of paired PM2.5 and CO data. Concentrations of PM2.5 during combustion activity, usually cooking, far exceeded background levels (no combustion activity): 97.9μg/m3 (IQR: 22.9–482.0), vs 7.6μg/m3, IQR: 2.5–20.6 respectively. Background PM2.5 concentrations were higher during daytime hours (11.7μg/m3 [IQR: 5.2–30.0] vs 3.3μg/m3 at night [IQR: 0.7–8.2]). Highest exposures were influenced by cooking location but associated with charcoal use (for CO) and firewood on a three-stone fire (for PM2.5). Cooking-related exposures were higher in more ventilated places, such as outside the household or on a walled veranda, than during indoor cooking. Conclusions: The study demonstrates the value of combining personal PM2.5 exposure data with detailed contextual information for providing deeper insights into pollution sources and influences. The finding of similar/lower exposures during cooking in seemingly less-ventilated places should prompt a re-evaluation of proposed clean air interventions in these settings.